Pengukuran Kesiapan Industri Minuman Teh Menjangkau Revolusi Industri 4.0 dengan Metode INDI 4.0 - Ekawati, Irna; Rahayu, Puji (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2021)
Rapid technological developments greatly affect the demand for products and services. So the industry needs to improve to maximize production achievements in order to meet market needs. The development of industry 4.0 provides an opportunity to revitalize the Indonesian manufacturing sector. Moreover, the Ministry of Industry has compiled "Making Indonesia 4.0" as a strategy and roadmap to develop industry 4.0 in Indonesia. Indonesia focuses on five main sectors for the development of industry 4.0, including the food and beverage, chemical, electronics, textile and clothing, and automotive industries. This research was conducted to determine the level of readiness of the manufacturing industry, especially the food and beverage industry at PT. Perkebunan Nusantara VIII to face industry 4.0 based on organizational and technological aspects. The measurement method used is the Indonesia Industry 4.0 Readiness Index (INDI 4.0). With these results, it can help the industry know the current level of achievement and know what needs to be done to get to the level of industry 4.0. Based on online and offline assessments carried out at the level of readiness, the people and culture aspects as well as the technology aspect have the highest level of use but are at Level 2. The technological aspect has the lowest readiness at Level 1. Overall, the company's readiness is at Level 1 (readiness stage). early) almost reached moderate readiness (Level 2).